Recent Advances in Aptamer-Based Biosensors for Detection of Pseudomonas aeruginosa - Zheng, Xin; Gao, Shunxiang; Wu, Jihong; Hu, Xiaobo (Frontiers in Microbiology, 2020)
Increasing concerns about nosocomial infection, food and environmental safety have prompted the development of rapid, accurate, specific and ultrasensitive methods for the early detection of critical pathogens. Pseudomonas aeruginosa is one of the most common pathogens that cause infection. It is ubiquitous in nature, being found in water, soil, and food, and poses a great threat to public health. The conventional detection technologies are either time consuming or readily produce false positive/negative results, which makes them unsuitable for early diagnosis and spot detection of P. aeruginosa. To circumvent these drawbacks, many efforts have been made to develop biosensors using aptamers as bio-recognition elements. Various aptamer-based biosensors for clinical diagnostics, food, and environmental monitoring of P. aeruginosa have been developed in recent years. In this review, we focus on the latest advances in aptamer-based biosensors for detection of P. aeruginosa. Representative biosensors are outlined according to their sensing mechanisms, which include optical, electrochemical and other signal transduction methods. Possible future trends in aptamer biosensors for pathogen detection are also outlined.